THE UTILISATION OF ISLAMIC FINTECH (I-FINTECH) IN PROMOTING SUSTAINABLE INCLUSIVE GROWTH: EVIDENCE FROM MICRO-ENTREPRENEURS IN MALAYSIA - Nik Hadiyan Nik Azman; Mohd Zaidi Md. Zabri; Tajul Ariffin Masron; Nurhafiza Abdul Kader Malim (Bank Indonesia, 2020)
Information technology is fundamentally changing the world today. The power of technology applicable fastly in Islamic financial technology (i-Fintech), as it expands access to mobile financial services. This is evidenced by the increasing number of customers who interact using technology, especially micro-entrepreneurs, who adopt the tools into their business models to tap into this opportunity to enhance their income. Therefore, it is imperative to examine the impact of i-fintech use in stabilising micro-entrepreneurs’ income. A quantitative technique was employed through the use of 120 questionnaires distributed to micro-entrepreneurs who had adopted i-fintech into their business. Using Amos and SEM models, the study indicates that crowdfunding, mobile money and peer-to-peer lending play a significant role in ensuring income sustainability for micro-entrepreneurs. The study also discusses both the theoretical and managerial implications in comprehending the determinants of sustainable income growth in Malaysia. The findings should help practitioners, researchers and regulators to have better understanding of the dynamics between the potential of i-fintech and sustainable income.